دور العلماء في الحياة السياسية في العصور الإسلامية الوسطى (Comprehensive Journal of Science, 2025)
This study examines the role of Muslim scholars (ʿulamāʾ) in political life during the medieval Islamic periods, viewing them as key actors in legitimizing authority, monitoring governance, and shaping the public sphere. It argues that the relationship between knowledge and power was not marginal; rather, it developed from early Islam and matured under the Umayyad and Abbasid states within major conceptual and legal frameworks such as the imamate, obedience conditioned by what is right, commanding right and forbidding wrong, and “Sharʿi governance” (siyāsa sharʿiyya). The study analyzes scholars’ direct participation through offices like the judiciary, ministerial advisory roles, and market supervision (ḥisba), as well as their indirect influence via fatwas, preaching, teaching, and public opinion formation. It also highlights the diversity of scholars’ stances—ranging from cooperation aimed at stability and institutional regulation to principled opposition when authority deviated from justice and law—illustrated by political ordeals such as the Mihna (the inquisition on the createdness of the Qur’an). The study concludes that scholars helped sustain a relative balance between ruler and ruled, and that scholarly independence was crucial to safeguarding justice and political legitimacy.
Keywords: ʿUlamāʾ, political authority, medieval Islamic periods, political legitimacy, siyāsa sharʿiyya, fatwa, scholarly opposition